Training periodization, methods, intensity distribution, and volume in highly trained and elite distance runners: A systematic review - Casado, A.; González-Mohíno, F.; González-Ravé, J. M.; Foster, C. (International Journal of Sports Physiology and Performance, 2022)
Purpose: This review aimed to determine (1) performance and training characteristics such as training intensity distribution (TID), volume, periodization, and methods in highly trained/elite distance runners and (2) differences in training volume and TID between event distances in highly trained/elite distance runners. Methods: A systematic review of the literature was carried out using the PubMed/MEDLINE, Scopus, and Web of Science databases. Results: Ten articles met the inclusion criteria. Highly trained/elite distance runners typically follow a pyramidal TID approach, characterized by a decreasing training volume from zone 1 (at or below speed at first ventilatory/lactate threshold [LT]) to zone 2 (between speeds associated with either both ventilatory thresholds or 2 and 4 mmol·L-1 LTs [vLT1 and vLT2, respectively]) and zone 3 (speed above vVT2/vLT2). Continuous-tempo runs or interval training sessions at vLT2 in zone 2 (ie, medium and long aerobic intervals) and those in zone 3 (ie, anaerobic or short-interval training) were both used at least once per week each in elite runners, and they were used to increase the number of either vLT2 or z3 sessions to adopt either a pyramidal or a polarized approach, respectively. More pyramidal- and polarized-oriented approaches were used by marathoners and 1500-m runners, respectively. Conclusions: Highly trained and elite middle- and long-distance runners are encouraged to adopt a traditional periodization pattern with a hard day-easy day basis, consisting in a shift from a pyramidal TID used during the preparatory and precompetitive periods toward a polarized TID during the competitive period.